AN ANALYSIS OF FACTORS INFLUENCING LEARNERSâ€™ ENGLISH SPEAKING FLUENCY AT JUNIOR HIGH SCHOOL - Halad Hulwana (ReALL - Research on Applied Linguistics and Literature, 2022)
There have been a lot of studies that already investigated the effects of the factors of speaking fluency, however not many were investigating the common factors influencing Learnersâ€™ English speaking fluency in Junior High School. This study was concerned about it. The participants were composed of 32 students of grade IX. The data were collected through questionnaires. Answers are measured through straightforward options with â€œyesâ€ or â€œnoâ€ options, and descriptive quantitative were used to explain the phenomenon in depth and within its real-world context by collecting data from students. As a result, the study discovered that there are some factorsthat affect English speaking fluency, they are cognitive and affective factors. The study could be used to help teachers better understand their studentsâ€™ speaking difficulties, and find appropriate ways to teach them efficiently.